2021
DOI: 10.3354/esr01108
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of endangered roseate terns and foraging habitat suitability around a colony in the western North Atlantic

Abstract: Predicting habitat suitability and understanding habitat utilization are important to inform and orient conservation and management decisions for the recovery of endangered species. In North America, the roseate tern Sterna dougallii is listed as endangered in both the northeastern USA and Canada, where little is known about the foraging spatial ecology of the species. We equipped breeding roseate terns with miniature GPS tracking devices during incubation at North Brother Island, the main Canadian colony. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Previous studies tracking roseate terns have found that adults restrict their foraging range to within 15 km of the colony during the incubation and early chickrearing periods of their lifecycles (Pratte et al 2021), but foraging range during the pre-breeding period is not known. After the adult terns have reached the breeding colonies post-migration, they forage in the vicinity of colonies to replenish energy reserves, engage in courtship, and build nests, but may be less spatially constrained during this time period (Cabot & Nisbet 2013).…”
Section: Interspecific Differences Between Roseate and Common Ternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies tracking roseate terns have found that adults restrict their foraging range to within 15 km of the colony during the incubation and early chickrearing periods of their lifecycles (Pratte et al 2021), but foraging range during the pre-breeding period is not known. After the adult terns have reached the breeding colonies post-migration, they forage in the vicinity of colonies to replenish energy reserves, engage in courtship, and build nests, but may be less spatially constrained during this time period (Cabot & Nisbet 2013).…”
Section: Interspecific Differences Between Roseate and Common Ternsmentioning
confidence: 99%
“…Radio-telemetry studies of roseate and common terns (e.g. Loring et al 2019, Pratte et al 2021) could inform spatial partitioning or overlap of foraging locations, how foraging range changes from the pre-breeding period to chick rearing, and how partitioning changes with shifting environmental and social conditions. Finally, prey availability can also shift throughout the breeding season (Safina & Burger 1985, Safina et al 1988.…”
Section: Interspecific Differences Between Roseate and Common Ternsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time, this included all known telemetry studies using devices enabling geographic positions of breeding seabirds in Atlantic Canada, plus additional data from common eiders from two colonies in Maine, USA, and from Leach's storm-petrel from one colony in France (Saint Pierre and Miquelon). These included unpublished data (Black, 2006;Symons, 2018;and other unpublished sources) as well as reassessment of previously published data on terns (Rock et al, 2007a;Rock et al, 2007b;Pratte et al, 2021), gulls (Maynard & Ronconi, 2018;Anderson et al, 2019;Shlepr et al, 2021), alcids (Regular et al, 2013Pratte et al, 2017;Gulka et al, 2019), northern gannet (Garthe et al, 2007;Garthe et al, 2011;Montevecchi et al, 2012), Leach's storm-petrel (Pollet et al, 2014;Hedd et al, 2018), and common eider (Mallory et al, 2020).…”
Section: Tracking Datamentioning
confidence: 99%
“…VHF data were obtained from studies of common and Arctic terns (Black, 2006;Rock et al, 2007a) which rely on aerial surveys to obtain location estimates, thus providing limited, but the only, tracking data available for these species. Roseate terns were tracked by VHF tags at Country Island (Rock et al, 2007b) and GPS at North Brother Island (Pratte et al, 2021). All tags were deployed on breeding adults.…”
Section: Tracking Datamentioning
confidence: 99%